Towards a Culture of Peace. A Contribution to the Debate - Delgado-Rojas, Jaime (2018)
In this essay, the Cantata de Santa María de Iquique serves as a framework for reflection on peace and otherness. It argues that the right to peace is an integral part of the legal and political ethic that involves the "others" towards whom it implies not simply tolerance, but respect for differences and conviviality. The range of relationships with the other is a swarm of ethical possibilities, stimulating and provocative, which places us on the level of the culture of peace and commitment to promote an education for peace and a strenghtened democracy.